ECONOMIES OF BEEKEEPING IN IRAQ - H. Al-Badri, B. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
There is no doubt that improving of economic performance of farms by using various factors of production available increases the participation rate of the agricultural sector in the GDP. The challenges those facing activity of beekeeping led to the departure of production units of this activity to achieve optimal productivity, which is employing economic resources used, and the level of economic and technical efficiency of these resources, so analyze the production economies and determine the level of technical efficiency are contribute a lot about the extent of the contribution of economic resources used in production and diagnose bugs and shortcomings down to put processors to ensure achieving the optimal use. The study aimed to analyze the economies of honey production and determine the levels of technical efficiency of beekeeping projects in the province of Baghdad for a random sample consisting of 50 beekeeper from Al-Madaen and Al-Mahmmodia in production year 2015. The analysis included a set of independent (explanatory) variables : the total number of workers, cages of queens, boxes of packages, the amount of the sugar nutrition, cans of treatment and frames, while the dependent variable is the quantity of honey, and using Stochastic Frontier Analysis (SFA) approach via using the Trans Log function. The results showed that the average of technical efficiency of sample of beekeepers was 85%, and that indicates a waste in the resources about 15% in average. The results also showed that the fixed costs ( especially the family labor) represent the great part of total costs because that their percentage were 57% from total costs, the study found that the sugar of nutrition consisted high percentage of the variable costs and its percentage is 33% from variable costs, besides there are rising in the cost of production. The study showed that most of beekeepers achieved high returns during the production year 2015. The estimation of parameters of function by the Ordinary Least Squares method (OLS) showed that there are a positive relationship among the amount of the honey production and workers, cans of treatment and frames, while it was a negative relationship with number of cells, number of cages of queens, number of boxes of packages and the amount of sugar of nutrition. The study recommended to reduce the quantity of inputs and the necessity of development of the industry of honey in Iraq through supporting the beekeepers.